The Dietary Inflammatory Index Is Associated with Prostate Cancer Risk in French Middle-Aged Adults in a Prospective Study(1)(2)(3) - Graffouillère, Laurie (J Nutr, 2016)
Background: Chronic inflammation is one of the mechanisms involved in carcinogenesis. Diet is a major source of pro- and anti-inflammatory compounds. The Dietary Inflammatory Index (DII) was designed to estimate its overall inflammatory potential. Objective: Our objective was to investigate the associations between the DII and overall, breast, and prostate cancer risks. Methods: This prospective study included 6542 participants [3771 women and 2771 men with a mean ± SD age of 49.2 ± 6.4 y and a BMI (in kg/m(2)) of 24.0 ± 3.6 at baseline] from the Supplémentation en VItamines et Minéraux AntioXydants (SU.VI.MAX) cohort who completed at least six 24-h dietary records during the first 2 y of follow-up. The DII was based on 36 food variables. Higher scores corresponded to more proinflammatory diets. A total of 559 incident cancers were diagnosed (median follow-up, 12.6 y), including 158 female breast and 123 prostate cancers (the 2 main cancer sites in this cohort). Associations were characterized by multivariable Cox proportional hazards models. Stratified analyses were performed according to the median of usual daily alcohol intake. Results: Sex-specific quartiles of the DII were positively associated with prostate cancer risk [quartile (Q) 4 compared with Q1, HR: 2.08; 95% CI: 1.06, 4.09] but not with overall or breast cancer risks. There was an interaction between the DII and alcohol intake (grams per day) on overall cancer risk (P-interaction = 0.02): the DII was positively associated with overall cancer risk in low-to-moderate alcohol drinkers (Q4 compared with Q1 HR: 1.75; 95% CI: 1.15, 2.68; P-trend = 0.02), whereas no association was detected in higher consumers of alcohol (P-trend = 0.8). This interaction was also observed for breast cancer (P-interaction = 0.001). Conclusion: Consistent with mechanistic data, findings from this study indicated that proinflammatory diets are associated with increased prostate cancer risk and, in low-to-moderate alcohol drinkers, with increased overall and breast cancer risk. The SU.VI.MAX trial was registered at clinicaltrials.gov as NCT00272428.